O que dizem as pesquisas atuais sobre o Atendimento Educacional Especializado para surdos. - Abreu, Thaís Magalhães (2021)
The purpose of this study is to identify in the articles published on the CAPES / MEC portal (Portal for the Improvement of Higher Education Personnel / Ministry of Education) how Specialized Educational Attendence (“Atendimento Educacional Especializado” - AEE) has been offered to deaf people in Brazil, starting in the year 2005 that is the year of Decree nº 5.626 publication. This study aimed to develop a qualitative research of an exploratory-descriptive character, being a bibliographic research. Nineteen articles with the proposed theme were selected, which, after reading and preliminary review, enabled the development of three analysis axes: "Centrality of Libras" (Brasilian Sign Language), "Mediation" and "Training of “AEE” professionals”. The analyzes and discussions were based on theoretical studies by Vigotski (2008) and on current research in the field of Deaf Education. From the data found, it can be seen that the practice does not always produce what is proposed by legislation and educational guidelines. As you may notice, Libras is very far from being considered the first language or instruction language in the “AEE” space, and that the training of professionals is below expectations, producing inadequate spaces and where teaching focuses on the Portuguese language. The deaf teacher is an unusual person in these spaces, but according to the findings, it was considered relevant to invest more in this sense, aiming to guarantee a space for the deaf teacher, which can bring benefits to the development of the deaf student.